In vivo imaging system (IVIS) therapeutic assessment of tyrosine kinase inhibitor-loaded gold nanocarriers for acute myeloid leukemia: a pilot study - Munteanu, Raluca-Andrada; Tigu, Adrian Bogdan; Feder, Richard; Tatar, Andra-Sorina; Gulei, Diana; Tomuleasa, Ciprian; Boca, Sanda (Frontiers in Pharmacology, 2024)
Acute Myeloid Leukemia (AML) is a malignancy in the myeloid lineage that is characterized by symptoms like fatigue, bleeding, infections, or anemia, and can be fatal if untreated. In AML, mutations in Tyrosine Kinases (TK) lead to enhanced tumor cell survival. The most frequent mutations in TK are reported in FLT3 (Fms-like tyrosine kinase 3), JAK2 (Janus kinase 2), and KIT (tyrosine-protein kinase KIT), making these TK potential targets for TK inhibitor therapies in AML. With 30% of the mutations in TKs, mutated FLT3 is associated with poor overall survival and an increased chance of resistance to therapy. FLT3 inhibitors are used in FLT3 mutant AML, and the combination with hypomethylating agents displayed promising results. Midostaurin (MDS) is the first targeted therapy in FLT3 mutant AML, and its combination with chemotherapy showed good results. However, chemotherapies induce several side effects and an alternative for chemotherapy might be the use of nanoparticles for better drug delivery, improved bioavailability, and reduced drug resistance and induced toxicity. The herein-presented study presents MDS encapsulated in gold nanoparticles and compared its efficacy with MDS alone, using both in vitro and in vivo models, using FLT3-ITD mutated AML cell line MV-4-11 Luc2 transfected to express luciferin. Our preclinical study suggests that MDS-loaded nanoparticles have a better tumor inhibitory effect compared to free drugs on in vivo models controlling the tumor growth in the first half of the treatment, while in the second part of the therapy, the tumor size was comparable to the cohort that was treatment-free.